MENTAL DISORDERS IN COMBATANTS WITH ACUTE STRESS DISORDER: DIAGNOSIS AND ASSESSMENT - Safin, Oleksandr; Chamlay, Inna (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . Psychological and psychiatric assistance to military personnel in modern warfare is provided through the phased evacuation of casualties, starting from the military medical support unit to rear medical facilities, depending on the severity of mental disorders. It is customary to distinguish three levels of mental disorders resulting from combat-related psychological trauma: pre-nosological, neurotic, and psychotic. As a rule, psychogenic disturbances are accompanied by physical injuries, which exacerbate the manifestations of mental disorders and create significant difficulties in medical triage due to the lack of effective and simple screening methods for the rapid diagnosis of severity and syndromic assessment of mental state. As a result, a certain percentage of military personnel with pre-nosological-level mental disorders are unnecessarily evacuated to subsequent stages.M e t h o d s . The Stanford Acute Stress Reaction Questionnaire was used, which allows for the retrospective assessment of the degree of mental disturbance at the time of combat trauma and the severity of subsequent PTSD symptoms based on dissociative symptoms. To assess the level of neuropsychological instability (NPI), the Module-Support (Module-S) was applied, which makes it possible to identify psychopathological symptoms in accordance with the diagnostic criteria outlined in sections F0–F6 ‘Organic, including symptomatic, mental disorders' of the ICD-10. Neurotic manifestations were evaluated using the Questionnaire for Neurotic Disorders – Symptomatic (ONR-Si) by E. Alexandrovich. The results were processed using mathematical and statistical methods of analysis in the Statistica 12 software package.R e s u l t s . The findings showed that the Stanford Acute Stress Reaction Questionnaire (SARS) provides a sufficiently reliable assessment of the level of mental disorders, unlike the Module-C and NDS-S questionnaires, where the range of extreme indicators overlapped between groups and did not allow for an unambiguous interpretation of the survey results. It was found that the largest group of combatants with acute stress disorder (49 %), who were at the hospitalisation stage, had a neurotic level of mental disorders, belonged to the category of temporary psychogenic losses, and required psychotherapeutic assistance. The second-largest group (36 %) had a pre-nosological level of mental disorders. These patients did not require further evacuation; instead, they needed psychological assistance with subsequent return to duty. Military personnel with psychogenic losses at the psychotic level accounted for 15 % and were referred for evacuation to rear medical facilities for specialized psychiatric care.C o n c l u s i o n s . The Stanford Acute Stress Reaction Questionnaire enables a reliable assessment of the level of mental disorders, is simple to administer, requires little time, and can be used as a rapid diagnostic tool for medical triage of patients with acute stress disorder during the rehabilitation stage in military hospitals. A total score of less than 50 points indicates a pre-nosological level; 51–90 points, a neurotic level; and 91 points or more, a psychotic level of mental disorders.
Keywords: combat mental trauma; neurotic symptoms; neuropsychological instability; acute stress reaction; acute stress disorder; levels of mental disorders